State Preschool Education Organization and Family Cooperation in Child Rearing - Karimova Mashkhura Rustamjon qizi; Khojakbarova Lolakhan Yusubovna (Periodica Journal, 2023)
The well-known Uzbek writer Abdulla Awlani's opinion on education, "For us, education is a matter of life, death, salvation, disaster, happiness, or joy" means that representatives of all nationalities can understand that personal education is not a private matter, but it is a. Raising a child is a long process.
Keywords: Raising; matter; education